2007
DOI: 10.1016/j.abb.2007.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the roles of putative active site residues in the oxalate decarboxylase from Bacillus subtilis

Abstract: Oxalate decarboxylase (OxDC) catalyzes the conversion of oxalate into CO(2) and formate using a catalytic mechanism that remains poorly understood. The Bacillus subtilis enzyme is composed of two cupin domains, each of which contains Mn(II) coordinated by four conserved residues. We have measured heavy atom isotope effects for a series of Bacillus subtilis OxDC mutants in which Arg-92, Arg-270, Glu-162, and Glu-333 are conservatively substituted in an effort to define the functional roles of these residues. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 36 publications
(88 reference statements)
6
81
3
Order By: Relevance
“…The extent to which active-site residues must be modified in order to change the substrate specificities of enzymes remains an interesting problem in enzyme evolution (23,44,55), and its resolution has important implications for efforts to redesign biological catalysts for biotechnological applications (11,31). The active sites of FRC and YfdW, however, are composed of conserved residues, making it difficult to understand (i) the observed differences in substrate specificity and (ii) the ability of oxalate to exhibit substrate inhibition only in the case of YfdW.…”
Section: Resultsmentioning
confidence: 99%
“…The extent to which active-site residues must be modified in order to change the substrate specificities of enzymes remains an interesting problem in enzyme evolution (23,44,55), and its resolution has important implications for efforts to redesign biological catalysts for biotechnological applications (11,31). The active sites of FRC and YfdW, however, are composed of conserved residues, making it difficult to understand (i) the observed differences in substrate specificity and (ii) the ability of oxalate to exhibit substrate inhibition only in the case of YfdW.…”
Section: Resultsmentioning
confidence: 99%
“…OxDC has garned attention due to its potentially numerous applications ranging from remediation of oxalate scaling in the wood and paper industry [13–16], bioengineering of crop plants for fungal resistance and lower oxalate content [17, 18], diagnostics and sensing of oxalate [1921], bioengineering of probiotic gut bacteria to release OxDC in the intestine [22], and as a dietary supplement for the degradation of excess oxalate in the stomach [23, 24]. Despite these efforts, significant questions remain about the details of the enzymatic mechanism of OxDC, and in particular about how modifications of the enzyme can direct its chemistry away from decarboxylase to oxidase activities [25]. …”
Section: Introductionmentioning
confidence: 99%
“…This mechanism requires oxygen to cycle through its 1-electron reduced state as superoxide which would likely be protonated in the pH range in which the enzyme is active [38]. Alternative proposals suggest one of the Mn ions undergoing a redox cycle between its +2 and +3 oxidation states allowing the associated dioxygen to remain a hydroperoxyl radical throughout the reaction [25, 27, 39]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a molecule of formate is coordinated to the N-terminal metal ion in one of the OxDC crystal structures (Anand et al, 2002). Third, recent work using OxDC mutants has shown that (i) site-directed mutagenesis of Glu162 (Svedružic et al, 2007) and (ii) modification of the N-terminal active site lid ) abolish decarboxylase activity. Although there is general agreement that Mn II in the N-terminal domain mediates OxDC-catalyzed decarboxylation, legitimate questions have been raised concerning the function (if any) of the Mn II bound in the C-terminal cupin domain.…”
Section: Oxalate Decarboxylase (Pdb: 1uw8)mentioning
confidence: 99%